THE USE OF ENGLISH OUTSIDE THE CLASSROOM: A NARRATIVE INQUIRY INTO STUDENTS' LANGUAGE EXPERIENCES IN REAL-LIFE CONTEXTS - Andewi, Widi; Putri, Lidya Ayuni (Journal of Linguistics and Social Sciences, 2025)
This study looks at how English Education students at a State Islamic University in Indonesia use English outside their classes. The research uses stories from students to understand their experiences. The researcher talked to ten students in interviews to learn about their reasons for using English, the problems they face, and how they try to improve. The study finds three main ideas. First, students have different reasons for using English, such as personal interest or outside pressure. Second, they have problems like feeling nervous and not knowing enough words. Third, they try to solve these problems by watching English videos, using social media, and studying with friends. Many students said they want to get better at speaking English and that using digital platforms helps them feel more comfortable and less afraid. This study gives useful ideas about learning English outside the classroom. It shows that motivation is important and that using English in daily life helps students learn better. It also connects to learning theories like Self-Determination Theory and explains how technology helps students practice English. The study suggests that teachers should think about these outside experiences when teaching English. It also encourages more research on different student groups and ways to help students with language problems.